2022
DOI: 10.31983/jrk.v11i1.8449
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Family Planning Dropouts in Women of Reproductive Age

Abstract: The Family Planning Program (FPP) is one of the strategies carried out by the government to suppress the increase in population growth. Unfortunately, women of reproductive age (WRA) often stop participating in FPP or drop it out, unaware of increasing the risk of conception. This study uses secondary data from the 2017 IDHS for 945 WRAs who have used modern FPP methods. It uses cross-tabulation to determine the distribution of husbands' approval regarding the FPP method, wanting more children, side effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…38 Side effects and health education are inhibiting factors of contraceptive use, 39 and the side effects mainly contribute to the discontinuation of contraceptive use. 15 Based on the age of women getting their first marriage, women who first married at the age of 20 years or younger had a higher percentage of contraception use (22.7%) than women who first married at 21 years of age or over (19.6%). Women married under 20 years of age were 1.25 times more likely to use a contraceptive compared to those who married later.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 Side effects and health education are inhibiting factors of contraceptive use, 39 and the side effects mainly contribute to the discontinuation of contraceptive use. 15 Based on the age of women getting their first marriage, women who first married at the age of 20 years or younger had a higher percentage of contraception use (22.7%) than women who first married at 21 years of age or over (19.6%). Women married under 20 years of age were 1.25 times more likely to use a contraceptive compared to those who married later.…”
Section: Resultsmentioning
confidence: 99%
“…36 In North Sumatra, women who had not reached the ideal number of children were more likely at risk of stopping contraception. 45 Couples of childbearing age usually limit their fertility through contraception if their plan for the ideal number of children is close, 35 or the desire for the children's sex composition is met. 46 This study indicated the opposite result to the study in Central Java, showing more frequent long-term contraceptive use among married women having two or fewer children alive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, various studies have also analyzed the effects of hormonal contraceptives on weight loss have been carried out in Northern Ethiopia by Zerihun et al (2019), in Southwest Nigeria (Odelola & Akadri, 2021), and in Indonesia by Kumala (2021) and Mas'udah et al (2021). In addition, previous studies focused on evaluating the attitudes and actions of 3-month injectable birth control acceptors in overcoming contraceptive side effects (Mamuroh et al, 2019), studying the characteristics and knowledge of birth control pill acceptors with consumption compliance (Virawati, 2023), analyzing knowledge of birth control acceptors with side effects of hormonal contraceptives with a duration of 3 months (Rismawanti, 2020), and examining the distribution of husbands' consent regarding family planning program methods, the desire to add children, side effects of family planning, the role of family planning service providers, and the incidence of drop out (Siregar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%